Caracterização funcional do mutante pkcAG579r que codifica o homólogo da proteína quinase C, no fungo patogênico aspergillus fumigatus - Rocha, Marina Campos (2013)
Over the recent years, the incidence of human fungal infections has shown a significant increase. Aspergillus fumigatus is a filamentous fungus opportunistic pathogen responsible for many human respiratory diseases, including invasive pulmonary aspergillosis, which is the most serious form of infection . Studies show that A. fumigatus virulence has a multifactorial process associated with its structure, capacity for growth, adaptation to stress conditions, evasion mechanisms of the immune system and ability to cause harm to the host. CWI (via cell wall integrity ) is a signaling cascade activated in yeast cells under conditions of cell wall stress and plays a role in the adaptation of various fungal pathogens in the human host . In many fungi , CWI is triggered by activation of protein kinase C ( PKC ) and that this pathway is associated with the transcription of genes related to maintaining the integrity of the cell wall and its redevelopment. In this work, a mutant Gly579Arg (G579R) was constructed by transformation mediated by inserting a gene replacement cassette comprising a G2044C transversion located in the cysteine-rich domain controller C1B pkcA of A. fumigatus. From the phenotypic analysis of the mutant strain was observed in the involvement of pkcAG579R CWI since the mutant showed high sensitivity to agents such as CR (congo red) and CFW (calcofluor white) . Furthermore, pkcA is also involved in tolerance to oxidative stress caused by paraquat and menadione. Additionally it was found to increase the sensitivity of the mutant pkcAG579R temperature variations as well as the inhibitor of Hsp90 radicicol. Como CWI is related to the transcriptional activation of biosynthetic genes and rugged cell wall (such as glucan synthase, glucanosil chitin synthases and transferases) the abundance of major genes coding for these enzymes was analyzed by RT-PCR in real time. Based on the tests can be α -1 ,3 glucan synthase ( agsA-C ) dependent signaling mediated PkcA for correct expression. Furthermore, genes such as β-1,3 glucan synthase (fksA) glucanosyltransferase (gelA-C) and some chitin synthases (chsB-E-C) appear not to be dependent function and CWI PkcA . These data demonstrated the role of pkcA signaling cascade in the maintenance of cell wall and thermotolerance in A. fumigatus. This work was the first in which a systematic analysis of gene pkcA was conducted in the human opportunistic fungal pathogen A. fumigatus.